Formulation, Analysis of Nutrient Content and Power Accept Crackers with Addition of Flour Red Spinach Leaves and Nike Fish Flour as Alternative Snack for School-Age Children - S., Salmin; Nurdiana, Nurdiana; Kariani, Ni Ketut (Poltekkes Kemenkes Jakarta III, 2024)
Students need adequate nutrients for their growth and development. Inadequate nutrition can lead to nutritional problems; anaemia is the most common among students. In 2018, the prevalence of anaemia in Central Sulawesi was 0.16%. This study aimed to determine the formulation of crackers, nutritional substances, and acceptability of the additional red spinach flour and Nike fish flour as an alternative snack. The method used for this study was experimental through a Random Design (RAL). The research was conducted from July 2–18, 2023. There were three formulations used with a comparison of red spinach flour and Nike fish flour: F1 (5%:35%), F2 (10%:30%), and F3 (15%:25%). Based on the results of organoleptic tests, it was found that there were significant differences in the colour, aroma, taste, and texture of crackers. The cracker's formula chosen was F3, which contained the following nutrients per 100 grams of water: 5.627%, ash 5.641%, protein 13.193%, fat 15.287%, carbohydrates 60.250%, iron 7.111 mg, and vitamin C 14,766 mg. It was concluded that crackers with the additional red spinach flour and Nike fish flour could achieve the nutritional needs as a contribution of snacks toward students' Recommended Dietary Allowances (RDA) by consuming the crackers in 50 grams of 18 pieces.